Preliminary studies on the molecular identification of sex in Taxus baccata L. - Zarek, Marcin (Leśne Prace Badawcze, 2016)
The scientific objective of this research was to screen random amplified polymorphic DNA (RAPD) and intersimple sequence repeat (ISSR) primers in order to find the molecular markers enabling the distinction between male and female individuals of the European yew. This is an initial step toward understanding the mechanisms of sex determination in this species. The study was conducted on European yew originating from two sites in Poland: the Zadni Gaj nature reserve near Cieszyn and the yew collection from the Botanical Garden of the Jagiellonian University in Krakow. In the present study, 716 random primers (696 RAPD primers: OPA -OPAI _1-16 and 20 ISSR primers marked as UBC) were tested to identify the sex in European yew by means of a modified bulked segregant analysis (BSA) method. The work was conducted in three stages, gradually limiting the number of primers through the elimination of primers that either did not exhibit any differences between the examined groups or did not provide amplification products. Among the tested primers, no ideal markers that would be present in all individuals of one sex but absent in the individuals of the other sex were found. However, some markers were found (A07_954, H13_729, J08_660, L12_390, U01_457, V14_527, AE03_941, AE03_1014) to occur with greater frequency in one sex. Using these, we further examined 13 band combinations (profiles) that were observed to occur only in male individuals and another 13 combinations that were observed only in female individuals, which could be used in the practical identification of sex. This is the first report to ascertain the sex of Taxus baccata trees, and it may help to determine the sex at an early stage of development.